Wobec cielesnej ekspansji – poetyckie reakcje - Przymuszała, Beata (Polonistyka. Innowacje, 2015)
The article is devoted to selected descriptions of the body in contemporary poetry, indicating the emergence of a reflection on the possibility of the actual experience of someone else's flesh in connection with the characteristic of the latest expansion of the culture of different images of human physicality. Tadeusz Różewicz's and Marcin Baran's poetic reflection (poets who are divided by one generation) reveals their common sense of difficulty concerning fulfillment arise from the close proximity of others. The discussed poem, in the article, by Czesław Miłosz concerns the vision of bodily rapprochement that transforms not only lovers but also the world around them. Important for the above examples is the conviction of the need to search for a language that would allow to write about these experiences (and, therefore, they often use this characteristic approach of poetic inexpressibility).